Landscape of Transcriptional Deregulations in the Preeclamptic Placenta - Vaiman, Daniel; Calicchio, Rosamaria; Miralles, Francisco (PloS one, 2013)
Preeclampsia is a pregnancy disease affecting 5 to 8% of pregnant women and a leading cause of both maternal and fetal mortality and morbidity. Because of a default in the process of implantation, the placenta of preeclamptic women undergoes insufficient vascularization. This results in placental ischemia, inflammation and subsequent release of placental debris and vasoactive factors in the maternal circulation causing a systemic endothelial activation. Several microarray studies have analyzed the transcriptome of the preeclamptic placentas to identify genes which could be involved in placental dysfunction. In this study, we compared the data from publicly available microarray analyses to obtain a consensus list of modified genes. This allowed to identify consistently modified genes in the preeclamptic placenta. Of these, 67 were up-regulated and 31 down-regulated. Assuming that changes in the transcription level of co-expressed genes may result from the coordinated action of a limited number of transcription factors, we looked for over-represented putative transcription factor binding sites in the promoters of these genes. Indeed, we found that the promoters of up-regulated genes are enriched in putative binding sites for NFkB, CREB, ANRT, REEB1, SP1, and AP-2. In the promoters of down-regulated genes, the most prevalent putative binding sites are those of MZF-1, NFYA, E2F1 and MEF2A. These transcriptions factors are known to regulate specific biological pathways such as cell responses to inflammation, hypoxia, DNA damage and proliferation. We discuss here the molecular mechanisms of action of these transcription factors and how they can be related to the placental dysfunction in the context of preeclampsia.